Minat Guru dalam menggunakan Media Pembelajaran Melalui Workshop Pembuatan Media Pembelajaran Interaktif Berbasis Kearifan Lokal Di Kabupaten Indragiri Hulu - Munjiatun, Munjiatun; Fendrik, Muhammad; Hermita, Neni; Melihayatri, Ningrum; Syahrilfuddin, Syahrilfuddin (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract This study aims to increase teachers' interest in creating learning media used in the teaching process. The learning media designed by teachers can help motivate students to be enthusiastic about learning, creating an enjoyable classroom atmosphere. The workshop process includes four stages: preparation, implementation, hands-on practice, and evaluation. The media creation workshop showed positive results in teachers' interest in using local wisdom-based learning media, both before and after the workshop. The results before the workshop were as follows: relevance (35%), ease of use (45%), perceived benefits (32.3%), facilities and infrastructure (55%), access to media (40%). After the workshop, the results were: relevance (72.5%), ease of use (75%), perceived benefits (85.5%), facilities and infrastructure (70%), access to media (69.5%). Although there was no significant increase, it has become an initial bridge for teachers to be interested and motivated to use learning media based on local wisdom.